One-Time Password Authentication System In Website - Azham Helmi, Azmi (2023)
The world we know how are mostly using the internet in any place and time in the world. We are connected to the social media, gaming platform, blog sites, business area, online shopping and much more every day without stopping. Internet can be useful however it has its own down side. Lately during the pandemic people are more and more connected to the internet because of movement control by several states to curb the spread of Covid-19. Because of that many hackers are taking advantage of this by stealing people information especially in websites. To counter this problem, one-time password authentication system is proposed in websites to protect the user from getting their account stolen or accessed by unauthorized users. This system will act as a second method of authentication next to the conventional login method. The method will send a one-time password that only can be accessed by the user to login into their account and cannot be used by hackers. This system is able to block any unauthorized hacker from meddling with user’s account and increase the security of the website that implements it.